2009
DOI: 10.1007/s12034-009-0039-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrocaloric effect of PMN-PT thin films near morphotropic phase boundary

Abstract: The electrocaloric effect is calculated for PMN-PT relaxor ferroelectric thin film near morphotropic phase boundary composition. Thin film of thickness, ∼ 240 nm, has been deposited using pulsed laser deposition technique on a highly (111) oriented platinized silicon substrate at 700°C and at 100 mtorr oxygen partial pressure. Prior to the deposition of PMN-PT, a template layer of LSCO of thickness, ∼ 60 nm, is deposited on the platinized silicon substrate to hinder the pyrochlore phase formation. The temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(70 citation statements)
references
References 18 publications
3
66
0
1
Order By: Relevance
“…In search of such materials, the EC experiment on PZ showed a maximum EC effect of 11.4 K on withdrawal of 40 MV/m [18]. Similar attempt to 0.63PMN-0.37PT thin film we found even better EC effect of 31 K on withdrawal of 75 MV/m [19]. The principle of EC effect is similar to vapor cycle refrigeration that consists of four steps.…”
Section: Solid-state Refrigerationsupporting
confidence: 61%
“…In search of such materials, the EC experiment on PZ showed a maximum EC effect of 11.4 K on withdrawal of 40 MV/m [18]. Similar attempt to 0.63PMN-0.37PT thin film we found even better EC effect of 31 K on withdrawal of 75 MV/m [19]. The principle of EC effect is similar to vapor cycle refrigeration that consists of four steps.…”
Section: Solid-state Refrigerationsupporting
confidence: 61%
“…Even with that, the entropy change is still ∼8 J/(kg K), which is not very high when compared with that of the materials with giant MCE (>20 J/(kg K)) [5,6]. Several more recent studies also reveal large ECEs in ferroelectric ceramic thin films [13][14][15][16][17]. It should be noted that, compared with bulk samples, thin films on foreign substrates will experience stresses from the substrates.…”
Section: Introductionmentioning
confidence: 94%
“…They have observed a temperature change of T ∼ 12 K under an electric field of 48 kV/mm, near anti-ferroelectric to paraelectric phase transition temperature (T c = 500 K). Saranaya et al [7] have also reported a temperature change of 31 K in 0.65PMN-0.35PT thin films by applying an electric field of ∼80 kV/mm at 413 K. But device application needs maximum ECE near room temperature (300 K). In view of this, ferroelectric materials especially relaxor ferroelectrics and polymers having transition temperature near 300 K are under investigation.…”
Section: Introductionmentioning
confidence: 99%